Territórios do fantástico em Pernambuco: o espaço em narrativas de Gilberto Freyre e Jayme Griz - Silva, Ivson Bruno da (2021)
Conditioned by the stigma of reality’s transgression, the fantastic literature created in Pernambuco has representations of the urban territory from Recife and its countryside regions. Works such as Assombrações do Recife velho, by Gilberto Freyre, and O lobishomem da porteira velha, by Jayme Griz accommodate an incognito and mysterious universe convicted by rational laws and cultivated by social imaginary side. Theming traditions, rites, mysticism, religiosity, and haunts which surround individuals, the books have their foundations on unexplainable circumstances which disturb human beings' daily life. Focusing on orders diktats which opposite to what is real, the current master’s thesis aims to analyze the space occupied with the fantastic on Gilberto Freyre’s report “O sobrado da Estrela” and in the tale of Jayme Griz “O lobishomem da porteira velha”. The exploration of the biographic and bibliographic aspects from Pernambuco authors antecedes investigation in nexus with the texts critical reception. With respect to the theorical propositions about the fantastic, Charles Nodier, Tzvetan Todorov, Irene Bessière, Felipe Furtado, Remo Ceserani and David Roas readings clear the comprehension about evolution of studies in the unusual fictional. About the literary specialty, there are presumptions from Antonio Candido, Osman Lins, Antonio Dimas and Luis Alberto Brandão’s validity on esthetic scope. On Gilberto Freyre’s report’s analysis, it’s possible to realize lofts are habitations for sights where spacial dynamics in and outside the houses is modified by uncommon actions of the ghosts. According to continuity with the contacts bonds, the narrative establishes correspondence between Recife’s haunts and the history of the city, marked by colonial and political-social struggles. In na analogous way, the fantastic way are on a noticeable spot at the agrarian world on Jayme Griz’ tale, amalgamated by regional beliefs from the mill, for the myth about the werewolf and alusions to folkloric and social cultural features. Frontier between possible and impossible is a farm gate in it, space where characters are threatened by supernatural irruption. On the dichotomous contrasts between urban and rural, real and unreal, intra and extratextual prisms, narratives engender a rupture with boards of reference of the reality and postulate the crisis between human convictions and the fantastic.